Effect of an increased thermal contact resistance in a salt PCM-graphite foam composite TES system. (June 2017) - Giménez, P.; Jové, A.; Prieto, C.; Fereres, S.
Abstract: Thermal Energy Storage systems using inorganic salts as Phase Change Materials (PCM) are ideal solutions for solar thermal direct steam generation power plants. However, the main limitation of these PCM is their low thermal conductivity. Though a composite PCM solution including graphite foam will increase the effective thermal conductivity of the storage material, the system performance is limited by the thermal contact resistance at the heat exchanger surface. An infiltrated PCM (sodium nitrate, NaNO3 ) in different commercial graphite foam structures, with variable porosity and apparent density is analyzed experimentally and numerically. The thermal properties of the PCM and the graphite matrix are experimentally determined to calculate effective properties of the composite. The performance of the composite PCM-graphite foam in a heat exchanger with embedded metallic tubes is analyzed for each foam type. During system operation, the difference in thermal expansion coefficients between the composite PCM and metallic tubes creates a void at the interface, which is gradually filled by the liquid salt. The effect on the discharge process of this low thermal conductivity layer forming around the steel tube is evaluated numerically, analyzing the deviation from the expected thermal performance of the ideal system. Highlights: Composite salt PCM with graphite foams are evaluated experimentally and numerically. A PCM layer at the heat exchanger surface increases the thermal contact resistance. Storage discharge is analyzed with a 1-D model. The added PCM layer can be equivalent to having a lower thermal conductivity foam.